2021
DOI: 10.1007/s11845-021-02668-2
|View full text |Cite
|
Sign up to set email alerts
|

Psychedelic perceptions: mental health service user attitudes to psilocybin therapy

Abstract: Introduction Despite the rapid advance of psychedelic science and possible translation of psychedelic therapy into the psychiatric clinic, very little is known about mental health service user attitudes. Objectives To explore mental health service user attitudes to psychedelics and psilocybin therapy. Methods A questionnaire capturing demographics, diagnoses, previous psychedelic and other drug use, and attitudes to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 82 publications
(77 reference statements)
0
10
1
Order By: Relevance
“…Translational Psychedelic science is evolving rapidly (1)(2)(3). Initial data suggests that the dose dependent, transient, altered state of information processing induced by psychedelics can be harnessed by the psychotherapeutic process to lead to clinical benefits across a range of disorders.…”
Section: Introductionmentioning
confidence: 99%
“…Translational Psychedelic science is evolving rapidly (1)(2)(3). Initial data suggests that the dose dependent, transient, altered state of information processing induced by psychedelics can be harnessed by the psychotherapeutic process to lead to clinical benefits across a range of disorders.…”
Section: Introductionmentioning
confidence: 99%
“…We propose that psychedelic research built on open and trusting PPI will result in superior outcomes and experiences for participants. The vocabulary used when developing participant information, outcome measures and interventions for psychedelic research might feel alienating or less socially acceptable to some audiences (72). Seeking the advice of others can help build empathy and help researchers to understand the fears and beliefs of potential participants of psychedelic research.…”
Section: Discussionmentioning
confidence: 99%
“…The uncertainty surrounding PAP was an important theme and showed that Psychiatrists are not just uncertain about their own role in PAP, but also the uncertain risks and benefits for patients. Recent research from Ireland suggested that just over a half of mental health service users would accept treatment with PAP if a doctor recommended it (18). It seems likely that psychiatrists will be increasingly asked about PAP by patients and be expected to have a working knowledge or who it benefits and how to access it.…”
Section: Discussionmentioning
confidence: 99%